Utilization of 5-Bromouracil by Thymineless Bacteria - Hewitt, Roger (1967)
Several thymineless Escherichia coli strains have been examined for their ability to replicate their deoxyribonucleic acid when bromouracil is substituted for thymine. The procedure we describe was used to identify a thymineless strain with characteristics relatively favorable to its use in bromouracil labeling experiments. In addition, mutants with an “absolute” thymine requirement could be easily distinguished from one with a “leaky” thymine requirement.